"Water-in-Salt" for Supercapacitors: A Compromise between Voltage, Power Density, Energy Density and Stability. Issue 3 (1st January 2018) - Lannelongue, Pierre; Bouchal, Roza; Mourad, Eléonore; Bodin, Charlotte; Olarte, Marco; le Vot, Steven; Favier, Frédéric; Fontaine, Olivier
Abstract : We report here electrochemical capacitors using an aqueous electrolyte based on the concept of "water-in-salt" with the aim to improve the energy density by increasing the voltage of the cell. A "water-in-salt" consists of a highly concentrated aqueous LiTFSI solution in which both volume and mass of LiTFSI are greater than those of water. With activated carbon supercapacitor electrodes (PICA) and 31 m "water-in-salt" electrolytes (m stands for molality), we were able to reach a cell voltage of 2.4 V whereas it is difficult to exceed 1.6 V in conventional aqueous devices because of water splitting. Moreover, it was observed that the specific capacitance of the cell is improved using "water-in-salt" electrolytes. In these conditions, an energy density of 30 Wh kg −1 was obtained which is at least three times greater than for conventional aqueous devices and in the same order of magnitude than for redox enhanced capacitors. Interestingly, fair stability, over 2000 cycles, was obtained for the 7 m electrolyte. Up to 90 sec charging-discharging rate, this latter electrolyte offers the best compromise between voltage, power and energy densities and stability. This study demonstrates the feasibility of water-in-salt as an electrolyte for supercapacitors and points out the most suited compositions for these electrolytes.